2010
DOI: 10.1016/j.ejcts.2009.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Discordant findings in patients with non-small-cell lung cancer: absolutely normal bone scans versus disseminated bone metastases on positron-emission tomography/computed tomography

Abstract: Discordant findings of skeletal metastasis between Tc-99m MDP bone scans and F-18 FDG PET/CT imaging may be seen in 20% of the patients with NSCLC. F-18 FDG PET/CT could detect metastatic bone involvement more accurately than bone scintigraphy. Bone scans are insensitive to early bone marrow neoplastic infiltration. Assessment of glucose metabolism with FDG PET/CT can represent a more powerful tool to detect early bone metastases in lung cancer than with traditional bone scans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 20 publications
0
13
0
1
Order By: Relevance
“…After the development of PET and PET/CT, however, it has been shown that PET and PET/CT are superior in the detection of osteolytic bone metastases [15,17]. This has been studied mainly in non small cell lung carcinoma, a disease in which bone metastases are usually osteolytic [26,27]. In breast cancer, due to the combination of osteolytic and sclerotic bone metastases, bone scintigraphy may remain of added value [28].…”
Section: Discussionmentioning
confidence: 96%
“…After the development of PET and PET/CT, however, it has been shown that PET and PET/CT are superior in the detection of osteolytic bone metastases [15,17]. This has been studied mainly in non small cell lung carcinoma, a disease in which bone metastases are usually osteolytic [26,27]. In breast cancer, due to the combination of osteolytic and sclerotic bone metastases, bone scintigraphy may remain of added value [28].…”
Section: Discussionmentioning
confidence: 96%
“…14,15 Sclerotic metastases are relatively acellular with lower volume of tumour tissues and less bone destruction than lytic lesions. 16,17 The sensitivity of lesion detection by the radiology resident was 57.7% on patient-based analysis through original CT reading. The reason for such low sensitivity was that the inexperienced radiologist often missed patients with single metastatic bone lesion on CT, especially when the lesion was small and sclerotic.…”
Section: Discussionmentioning
confidence: 99%
“…62 Results of 99m Tc MDP and FDG PET/CT for bone involvement have been shown to be discordant in up to 20% of patients with lung cancer, primarily because 99m Tc MDP cannot identify early metastatic bone marrow infiltration. 64 Although uptake of FDG in bone can occur on PET studies before radiologically evident bone destruction, inflammatory conditions can also cause focal uptake. For this reason, biopsy or correlation with anatomic imaging studies is mandated to confirm an osseous metastasis before choosing a treatment regimen, if it is the sole abnormality.…”
Section: Metastasismentioning
confidence: 99%